2006
DOI: 10.1111/j.1468-1293.2006.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of the effect of atazanavir on the QTc interval and QTc dispersion in HIV‐positive patients

Abstract: Southwestern Medical Center at Dallas,and 6 Veterans Affairs North Texas Health Care System, Dallas, TX, USA Background Atazanavir (ATV), an HIV protease inhibitor (PI) that may be preferred for the treatment of HIV-infected patients with cardiovascular comorbidities because of its favourable effects on plasma lipids, has been associated with cardiac rhythm disturbances. ObjectiveTo quantify the effect of ATV on corrected QT (QTc) and QTc dispersion (QTd), markers of the potential for cardiac dysrhythmia, in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 31 publications
7
57
1
2
Order By: Relevance
“…ATV has a peak free concentration of 0.18-1.06 μmol/L, which is less than the IC 50 value of 5.7±1.8 μmol/L obtained in our results. This result could explain the lack of a significant influence of PI on QTc prolongation, which is consistent with the recent data showing that ATV has no effect on ventricular repolarization with repeated administration [11] .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…ATV has a peak free concentration of 0.18-1.06 μmol/L, which is less than the IC 50 value of 5.7±1.8 μmol/L obtained in our results. This result could explain the lack of a significant influence of PI on QTc prolongation, which is consistent with the recent data showing that ATV has no effect on ventricular repolarization with repeated administration [11] .…”
Section: Discussionsupporting
confidence: 81%
“…Similar to other PIs [4][5][6][7] , ATV has previously been reported to be specifically associated with acquired long-QT syndrome, druginduced QT prolongation, and torsades de pointes (TdP) in HIV-infected patients [8][9][10] . However, these results contradict other recently published studies [11,12].…”
Section: Introductioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In the present study, no 24-h sympathetic enhancement was observed in any group. Although it has been shown that antiretroviral drugs do not affect the QT or QTc intervals (40), as also found in the present findings, further studies monitoring QT interval adaptation are warranted as new drugs appear on this scenario.…”
Section: Discussionmentioning
confidence: 43%
“…O uso do ATV na terapia antirretroviral também foi associado ao bloqueio atrioventricular de primeiro grau 14 .…”
Section: Discussionunclassified